Pengaruh Budaya Organisasi dan Perilaku Organisasi Terhadap Kinerja Karyawan pada Ditjen Perbendaharaan Republik Indonesia di Kanwil Provinsi DKI Jakarta - Robby Nugroho; Ignatius Ario Sumbogo (UNIVERSITAS KALBIS, 2022)
This study aims to analyze the effect of the influence of organizational culture and organizationel behavior on the performance of employees of the Directorate General of Treasury of the Republic of Indonesia in the Regional Office of DKI Jakarta Province. This study uses a quantitative approach. Methods of collecting data using a questionnaire. The research method uses multiple analysis regression. The population in the study of employees working at the Directorate General of Treasury of the Republic of Indonesia in the Regional Office of the DKI Jakarta Province. The sampling technique used saturated samples to 50 respondents. The results of hypothesis testing indicate that organizational culture has a significant effect on employee performance. Likewise organizational behavior has a significant influence on employee performance. The conclusion of this study is that organizational culture and organizational behavior have a significant effect on employee performance.